In vivo administration of dental epithelial stem cells at the apical end of the mouse incisor - Orsini, Giovanna; Jimenez-Rojo, Lucia; Natsiou, Despoina; Putignano, Angelo; Mitsiadis, Thimios A. (Frontiers in Physiology, 2015)
Cell-based tissue regeneration is an attractive approach that complements traditional surgical techniques for replacement of injured and lost tissues. The continuously growing rodent incisor provides an excellent model system for investigating cellular and molecular mechanisms that underlie tooth renewal and regeneration. An active population of dental epithelial progenitor/stem cells located at the posterior part of the incisor, commonly called cervical loop area, ensures the continuous supply of cells that are responsible for the secretion of enamel matrix. To explore the potential of these epithelial cells in therapeutic approaches dealing with enamel defects, we have developed a new method for their in vivo administration in the posterior part of the incisor. Here, we provide the step-by-step protocol for the isolation of dental epithelial stem cells and their delivery at targeted areas of the jaw. This simple and yet powerful protocol, consisting in drilling a hole in the mandibular bone, in close proximity to the cervical loop area of the incisor, followed up by injection of stem cells, is feasible, reliable, and effective. This in vivo approach opens new horizons and possibilities for cellular therapies involving pathological and injured dental tissues.